Borate Transporters and SLC4 Bicarbonate Transporters Share Key Functional Properties - Jean L. Beltran; Lila G. McGrath; Sophia Caruso; Richara K. Bain; Claire E. Hendrix; Hana Kamran; Hartlee G. Johnston; Rebecca M. Collings; Menkara-Chinua N. Henry; Tsega-Ab L. Abera; Valeria A. Donoso; Erin C. Carriker; et al. (Membranes, 2023)
Borate transporters are membrane transport proteins that regulate intracellular borate levels. In plants, borate is a micronutrient essential for growth but is toxic in excess, while in yeast, borate is unnecessary for growth and borate export confers tolerance. Borate transporters share structural homology with human bicarbonate transporters in the SLC4 family despite low sequence identity and differences in transported solutes. Here, we characterize the S. cerevisiae borate transporter Bor1p and examine whether key biochemical features of SLC4 transporters extend to borate transporters. We show that borate transporters and SLC4 transporters share multiple properties, including lipid-promoted dimerization, sensitivity to stilbene disulfonate-derived inhibitors, and a requirement for an acidic residue at the solute binding site. We also identify several amino acids critical for Bor1p function and show that disease-causing mutations in human SLC4A1 will eliminate in vivo function when their homologous mutations are introduced in Bor1p. Our data help elucidate mechanistic features of Bor1p and reveal significant functional properties shared between borate transporters and SLC4 transporters.